فعالية نموذج التعليم التعاوني من نوع رمي كرة الثلج في تعليم مهارة الكتابة في المدرسة الابتدائية سولور سيوو - Sari, Devina Kurnia (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
ABSTRACT Among the four language skills in learning Arabic, writing skills (kitabah) are the most complex and highest-level language skills, because writing skills will not come automatically, but must go through lots and regular practice. Especially if learning Arabic is intended for elementary school age students. Because elementary school age students have a short focus, various kinds of innovative learning model are needed so that students don't feel bored. The purpose of this research is to find out the effectiveness of writing skills learning using the snowball throwing type cooperative learning model at MI PSM Sulursewu, Ngawi, East Java. The approach used in this research is a quantitative approach to the type of experimental research. The research instruments used in this study were observation, tests(pre and post test), questionnaires and documentation. This research was conducted in class 5A with 24 students and 5B with 23 students at MI PSM Sulursewu. The results of this research, because the data is not normally distributed, researchers use the Mann Whitney test. The Mann Whitney test results show that the asymp.sig (2-tailed) value is 0.011, which is smaller than the probability value of 0.05 and can be concluded that the use of the snowball throwing type cooperative learning model in writing skills learning is effective.